Chemical, isotopic and mineral compositions of basal metalliferous sediments from DSDP Legs 5 and 7 - Jack R Dymond; John B Corliss; G Ross Heath; Cyrus W Field; E Julius Dasch; H Herbert Veeh (PANGAEA, 1973)
Sediments from near the basement of a number of Deep Sea Drilling Project (DSDP) sites, from the Bauer Deep, and from the East Pacific Rise have unusually high transition metal-to-aluminum ratios. Similarities in the chemical, isotopic, and mineralogical compositions of these deposits point to a common origin. All the sediments studied have rare-earth-element (REE) patterns strongly resembling the pattern of sea water, implying either that the REE extquotesingles were coprecipitated with ferromanganese hydroxyoxides (hydroxyoxides denote a mixture of unspecified hydrated oxides and hydroxides), or that they are incorporated in small concentrations of phosphatic fish debris found in all samples. Oxygen isotopic data indicate that the metalliferous sediments are in isotopic equilibrium with sea water and are composed of varying mixtures of two end-member phases with different oxygen isotopic compositions: an iron-manganese hydroxyoxide and an iron-rich montmorillonite. A low-temperature origin for the sediments is supported by mineralogical analyses by x-ray diffraction which show that goethite, iron-rich montmorillonite, and various manganese hydroxyoxides are the dominant phases present. Sr87/Sr86 ratios for the DSDP sediments are indistinguishable from the Sr87/Sr86 ratio in modern sea water. Since these sediments were formed 30 to 90 m.y. ago, when sea water had a lower Sr87/Sr86 value, the strontium in the poorly crystalline hydroxyoxides must be exchanging with interstitial water in open contact with sea water. In contrast, uranium isotopic data indicate that the metalliferous sediments have formed a closed system for this element. The sulfur isotopic compositions suggest that sea-water sulfur dominates these sediments with little or no contribution of magmatic or bacteriologically reduced sulfur. In contrast, ratios of lead isotopes in the metalliferous deposits resemble values for oceanic tholeiite basalt, but are quite different from ratios found in authigenic marine manganese nodules. Thus, lead in the metalliferous sediments appears to be of magmatic origin. The combined mineralogical, isotopic, and chemical data for these sediments suggest that they formed from hydrothermal solutions generated by the interaction of sea water with newly formed basalt crust at mid-ocean ridges. The crystallization of solid phases took place at low temperatures and was strongly influenced by sea water, which was the source for some of the elements found in the sediments.